Problem gambling and associated mental health concerns in elite athletes: a narrative review. Issue 12 (22nd June 2019) - Derevensky, Jeffrey Lee; McDuff, David; Reardon, Claudia L; Hainline, Brian; Hitchcock, Mary E; Richard, Jeremie
Abstract : Opportunities to participate in gambling have dramatically changed during the past 20 years. Casinos have proliferated as have electronic gambling machines, lotteries, sports betting, and most recently online gambling. Gambling among the general population has moved from being perceived negatively to a socially acceptable pastime. As over 80% of individuals have reported gambling for money during their lifetime, governments recognise that regulating gambling—a multibillion dollar industry—is a significant source of revenue. While the vast majority of individuals engaged in some form of gambling have no or few gambling-related problems, an identifiable proportion of both adolescents and adults experience significant gambling-related problems. Elite athletes have not been immune to the lure of gambling nor its concomitant problems. Prevalence studies suggest higher rates of gambling problems among athletes than the general population. In this narrative review, we examine several risk factors associated with gambling problems among elite athletes and new forms of gambling that may be problematic for this population. Given the potential serious mental health and performance consequences associated with a gambling disorder for athletes, we aim to increase coaches', athletic directors' and health professionals' knowledge concerning the importance of screening and treatment referrals.